2018
DOI: 10.12968/jowc.2018.27.11.744
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fluorescence biomodulation in the real-life management of chronic wounds: the EUREKA trial

Abstract: Objective: Fluorescence biomodulation (FB), a form of photobiomodulation (PBM) that is also known as low energy level light (LELL), has become an increasingly used clinical tool to induce wound healing in wounds that remain recalcitrant to treatment. In a real-life clinical setting, the aim of the EUREKA (EvalUation of Real-lifE use of Klox biophotonic system in chronic wound mAnagement) study was to confirm the efficacy and safety of LumiHeal, a system based on FB, in the treatment of chronic wounds such as v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 36 publications
5
25
0
2
Order By: Relevance
“…The lack of significant statistical differences between groups in the clinical secondary outcomes (Pruritus Severity Scale; Pain Severity Score; Aural temperature) helps demonstrate that LIG can have at least an equivalent clinical effect to the standard of care chosen. These results are very encouraging and well in line with the previous results reported with FB systems in humans suffering from diseases of QW group receiving LIG once weekly, BW group receiving LIG twice weekly, C group receiving standard of care twice daily, sd standard deviation, T 0 first evaluation time, T 5 sixth (last) evaluation time the skin, capable of accelerating healing, with reduced pain, and minimizing the clinical signs of bacterial colonization [22,29,32,[46][47][48][49][50]. Poly-microbial colonization often occurs in otitis externa and the continuum between mild-moderate colonization and the beginning of infection are blurred [51][52][53].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The lack of significant statistical differences between groups in the clinical secondary outcomes (Pruritus Severity Scale; Pain Severity Score; Aural temperature) helps demonstrate that LIG can have at least an equivalent clinical effect to the standard of care chosen. These results are very encouraging and well in line with the previous results reported with FB systems in humans suffering from diseases of QW group receiving LIG once weekly, BW group receiving LIG twice weekly, C group receiving standard of care twice daily, sd standard deviation, T 0 first evaluation time, T 5 sixth (last) evaluation time the skin, capable of accelerating healing, with reduced pain, and minimizing the clinical signs of bacterial colonization [22,29,32,[46][47][48][49][50]. Poly-microbial colonization often occurs in otitis externa and the continuum between mild-moderate colonization and the beginning of infection are blurred [51][52][53].…”
Section: Discussionsupporting
confidence: 88%
“…In this context, photobiomodulation (PBM) is widely known for its therapeutic benefits in the protection and regeneration of tissues [18][19][20][21][22][23]. Studies have demonstrated that PBM can reduce pain and inflammation [23][24][25], improve cancer management [26], and stimulate healing and tissue repair [20][21][22][27][28][29][30][31]. PBM is defined by the use of visible light to stimulate biological functions in a non-thermal and non-cytotoxic manner.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One pilot study of five dogs reported the beneficial effects of low‐level laser therapy (a form of PBM) in sterile pyogranulomatous pododermatitis cases; a larger study failed to report an improvement in pedal pruritus and pedal lesions scores in atopic dogs . The KLOX Fluorescence Biomodulation System (KFBS) consists of a blue light‐emitting diode (LED) device and a topical photoconverter gel, which when illuminated by the LED device, emits low‐energy light in the form of fluorescence . In vivo and in vitro studies have shown that KBFS can modulate inflammatory mediators [such as tumor necrosis factor (TNF)‐α and interleukin (IL)‐6] and stimulate growth factors [such as transforming (TGF)‐ß, fibroblast (FGF), platelet‐derived (PDGF) and vascular endothelial (VEGF) growth factors].…”
Section: Introductionmentioning
confidence: 99%